Educational intervention in the context of the classroom for the inclusion of students with attention deficit hyperactivity disorder in general education schools in Huambo - Baca , Laurinda; David, Celso Henrique; Henrique, Carlos Gabriel; Utengi, Celestino (Seven Editora, 2023)
The present research arises from the fact that it is verified in the students in the context of the classroom frequent distractions in the face of any stimulus, lack of attention when the teacher explained the contents, in the performance of tasks, constantly getting up from their seats and not only. Based on the above, the following problem was formulated: What methodological strategies can the teacher use to carry out the educational intervention of students with Attention Deficit Hyperactivity Disorder in the context of the classroom, from the perspective of inclusive education? Thus, the general objective was to empower teachers with methodological strategies that allow them to carry out educational intervention in the context of the classroom, from the perspective of inclusive education of students with Attention Deficit Hyperactivity Disorder. The study is descriptive, with a mixed approach. Theoretical methods were used: historical-logical , analysis-synthesis and bibliographic research. And the empirical ones: observation, interview, and questionnaire. For data treatment, the statistical method was used with the support of the SPSS statistical program. 20.0. The results show that there are difficulties in teachers in the educational intervention of students with ADHD from the perspective of inclusion in the context of the classroom, due to weaknesses in knowledge of methodological strategies to care for students with ADHD. The proposed strategy includes continuous training activities to enhance teachers’ knowledge about ADHD identification and to carry out educational intervention from the perspective of inclusion using organizational strategies, positive behavior, strategies for students with ADHD to carry out assessments/tests and intervention activities in the classroom. DOI:https://doi.org/10.56238/sevened2023.006-093